2010
DOI: 10.1186/1741-7015-8-44
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inducible factor 1α gene (HIF-1α) splice variants: potential prognostic biomarkers in breast cancer

Abstract: BackgroundHypoxia-inducible factor 1 (HIF-1) is a master transcriptional regulator of genes regulating oxygen homeostasis. The HIF-1 protein is composed of two HIF-1α and HIF-1β/aryl hydrocarbon receptor nuclear translocator (ARNT) subunits. The prognostic relevance of HIF-1α protein overexpression has been shown in breast cancer. The impact of HIF-1α alternative splice variant expression on breast cancer prognosis in terms of metastasis risk is not well known.MethodsUsing real-time quantitative reverse transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 33 publications
(47 reference statements)
0
38
2
Order By: Relevance
“…[28][29][30][31][32] However, our results showed an important correlation between the expression of HIF-1a and cell proliferation. In addition, we found that the expression of HIF-1a was in part dependent on glycolysis, suggesting that in the early stages of MF, the synthesis of HIF-1a is at least partially dependent on proliferating T cells that follow a glycolytic pathway instead of oxidative phosphorylation.…”
contrasting
confidence: 52%
See 1 more Smart Citation
“…[28][29][30][31][32] However, our results showed an important correlation between the expression of HIF-1a and cell proliferation. In addition, we found that the expression of HIF-1a was in part dependent on glycolysis, suggesting that in the early stages of MF, the synthesis of HIF-1a is at least partially dependent on proliferating T cells that follow a glycolytic pathway instead of oxidative phosphorylation.…”
contrasting
confidence: 52%
“…27 In malignant tissues, HIF-1a regulates cellular metabolism and the transcription of cytokines and growth factors associated with malignant neoplasias. [28][29][30][31] In several studies, the increased expression of HIF-1a has been correlated with the progression, aggressiveness and poor prognosis of numerous types of cancer, including lymphoma. 26,32 In addition, there is evidence that HIF-1a can negatively regulate the T-cell response.…”
Section: Mycosis Fungoides (Mf) Is the Most Common Clinical Variant Omentioning
confidence: 99%
“…RNA was isolated using the RNeasy Mini Kit (Qiagen, Hilden, Germany), according to the manufacturer's instructions. Real-time PCR (primer and probe) for HIF1a was performed as previously described by Dales et al 14 Abl quantified by real-time PCR as published earlier was used as housekeeping gene. 15 Quantification of RNA transcript expression was normalized determining the ratio between expression levels of targets and Abl.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Zhang and co-workers showed that EBV miRNAs (miR-BART7 and miR-BART13) can serve as important biomarkers for NPC diagnosis and prediction of treatment efficacy [58]. The potential prognostic value of EGFR and HIF1α has been previously demonstrated in breast and prostate cancers [60,61]. It would be interesting if these proteins can also be used as prognostic markers for EBV-related cancers.…”
Section: Novel Implications Of Exosomes In Diagnosis and Treatment Ofmentioning
confidence: 99%